Glioblastoma in the elderly: making sense of the evidence - Mason, Matthew (Neurooncol Pract, 2016)
Glioblastoma is a highly malignant neoplasm, notorious for its poor prognosis. The median age of diagnosis is 64 years, with an increasing number of patients diagnosed over the age of seventy. Managing elderly patients with this condition is challenging. Management pathways may include surgery, radiotherapy, chemotherapy, and best supportive care. Many clinical trials in oncology exclude elderly patients, including some of those for malignant brain tumors, leaving less evidence to guide treatment in these patients. Recent advances in molecular diagnostics and biomarkers, such as 06-methylguanine-DNA-methyltransferase (MGMT) promoter methylation status, may help guide optimal treatment selection. Focusing on available randomized data, this review provides a practical overview of the evidence for treating newly diagnosed glioblastoma in the elderly, including management recommendations.